2018
DOI: 10.3201/eid2405.170829
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Spirochetemia and Early PCR Detection of Borrelia miyamotoi

Abstract: We investigated whether Borrelia miyamotoi disease can be detected in its early stage by using PCR for borrelial 16S rRNA, which molecule (DNA or RNA) is the best choice for this test, and whether spirochetes are present in blood during the acute phase of B. miyamotoi disease. A total of 473 patients with a suspected tickborne infection in Yekaterinburg, Russia, in 2009, 2010, and 2015 were enrolled in this study. Blood samples were analyzed by using quantitative PCR or ELISA, and a diagnosis of borreliosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
2
38
0
5
Order By: Relevance
“…syndrome. It complements the Russian study by Karan et al published in 2018 (28), which was conducted at the early stage on patients presenting with acute symptoms after a tick bite.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…syndrome. It complements the Russian study by Karan et al published in 2018 (28), which was conducted at the early stage on patients presenting with acute symptoms after a tick bite.…”
Section: Discussionsupporting
confidence: 58%
“…Erythema migrans was observed in 16.1% of the patients, but data are insufficient to rule out a previous infection with B. burgdorferi s.l. However the responsibility of B. miyamotoi in some cases of erythema migrans is probable since, in the study looking at the early stage of the tick-borne infection, 3% of patients with an erythema migrans had a positive blood PCR for B. miyamotoi (28). Our data suggest that the disease may be persistent, even on the long term and that this species of Borrelia may not cross-react with B. burgdorferi serology.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…in human specimens, thus challenging prevailing thought regarding geographic distribution and prevalence of RFB infection [15]. For example, a recent study reported that approximately 23% of a cohort of 301 patients in Russia with confirmed Borrelia infection demonstrated positive molecular testing for B. miyamotoi [31]. RFB is also a growing concern in the Western USA, Central America, and South America [13,32].…”
Section: Discussionmentioning
confidence: 99%
“…This test will be used in clinical practice in the future and it will improve serologic examination in clinical studies [10]. Therefore, molecular tests (PCR or real time PCR) are more appropriate and reliable methods for routine diagnosis at this moment [2,11].…”
Section: Introductionmentioning
confidence: 99%